Investigation of the causal etiology in a patient with T-B+NK+ immunodeficiency - Sertori, Robert; Lin, Jian-Xin; Martinez, Esteban; Rana, Sadhna; Sharo, Andrew; Kazemian, Majid; Sunderam, Uma; Andrake, Mark; Shinton, Susan; Truong, Billy; Dunbrack, Roland M.; Liu, Chengyu; et al. (Frontiers in Immunology, 2022)
Newborn screening for severe combined immunodeficiency (SCID) has not only accelerated diagnosis and improved treatment for affected infants, but also led to identification of novel genes required for human T cell development. A male proband had SCID newborn screening showing very low T cell receptor excision circles (TRECs), a biomarker for thymic output of nascent T cells. He had persistent profound T lymphopenia, but normal numbers of B and natural killer (NK) cells. Despite an allogeneic hematopoietic stem cell transplant from his brother, he failed to develop normal T cells. Targeted resequencing excluded known SCID genes; however, whole exome sequencing (WES) of the proband and parents revealed a maternally inherited X-linked missense mutation in MED14 (MED14V763A), a component of the mediator complex. Morpholino (MO)-mediated loss of MED14 function attenuated T cell development in zebrafish. Moreover, this arrest was rescued by ectopic expression of cDNA encoding the wild type human MED14 ortholog, but not by MED14V763A, suggesting that the variant impaired MED14 function. Modeling of the equivalent mutation in mouse (Med14V769A) did not disrupt T cell development at baseline. However, repopulation of peripheral T cells upon competitive bone marrow transplantation was compromised, consistent with the incomplete T cell reconstitution experienced by the proband upon transplantation with bone marrow from his healthy male sibling, who was found to have the same MED14V763A variant. Suspecting that the variable phenotypic expression between the siblings was influenced by further mutation(s), we sought to identify genetic variants present only in the affected proband. Indeed, WES revealed a mutation in the L1 cell adhesion molecule (L1CAMQ498H); however, introducing that mutation in vivo in mice did not disrupt T cell development. Consequently, immunodeficiency in the proband may have depended upon additional, unidentified gene variants. MED14 is thus a candidate primary immunodeficiency gene.